2019
DOI: 10.1536/ihj.18-659
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rupture Due to Reinfarction in the Early Phase of Apical Myocardial Infarction

Abstract: A 72-year-old woman with hypertension, dyslipidemia, and diabetes mellitus presented to our hospital because of the sudden onset of chest pain. Emergency coronary angiography showed acute occlusion of the distal left anterior descending artery and coronary intervention with a drug-eluting stent was performed. Sudden cardiopulmonary arrest occurred on the sixth day of hospitalization, but coronary angiography showed no remarkable progression of the coronary artery diseases, including the site of stent implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Unsurprisingly, there was no consensus on the prevention and treatment of FWR. [6][7][8][9][10] FWR is associated with a high mortality from electromechanical dissociation or pericardial tamponade and is often unresponsive to resuscitative maneuver. Our knowledge of FWR is limited to case reports and retrospective studies frequently combining it to ventricular septal rupture (VSR) and/or papillary muscle rupture (PMR).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, there was no consensus on the prevention and treatment of FWR. [6][7][8][9][10] FWR is associated with a high mortality from electromechanical dissociation or pericardial tamponade and is often unresponsive to resuscitative maneuver. Our knowledge of FWR is limited to case reports and retrospective studies frequently combining it to ventricular septal rupture (VSR) and/or papillary muscle rupture (PMR).…”
mentioning
confidence: 99%
“…Our knowledge of FWR is limited to case reports and retrospective studies frequently combining it to ventricular septal rupture (VSR) and/or papillary muscle rupture (PMR). [4][5][6][10][11][12] However, obviously, differences between FWR and VSR/PMR exist, such as incidence, clinical manifestations, and risk factors. 6,11,13) Different from the clinical manifestation of FWR, VSR, and PMR patients often progress to refractory heart failure.…”
mentioning
confidence: 99%
“…Therefore vulnerable myocardium easily tear, dislodgement by lead tension after CIED implantation may increase [ 19 ]. Some autoimmune diseases, for which immunosuppressive therapy is indicated, cause myocardial injury, including inflammation, fibrosis, and necrosis [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The incidence of cardiac rupture after acute myocardial infarction has decreased over the past two decades with the emergence of primary coronary intervention and the progression of drug therapy. [7,9,10] The incidence of cardiac rupture has been reported to range from about 1% to 3% after acute myocardial infarction, but autopsy research has shown that cardiac rupture is involved in 30% to 65% of in-hospital acute myocardial infarction-induced death. [9] This complication of acute myocardial infarction is more common in women, hypertensive patients, and patients who have had myocardial infarction for the first time over the age of 60 years, but these characteristics are not specific enough to identify patients at high risk of cardiac rupture.…”
Section: Introductionmentioning
confidence: 99%
“…[7,9,10] The incidence of cardiac rupture has been reported to range from about 1% to 3% after acute myocardial infarction, but autopsy research has shown that cardiac rupture is involved in 30% to 65% of in-hospital acute myocardial infarction-induced death. [9] This complication of acute myocardial infarction is more common in women, hypertensive patients, and patients who have had myocardial infarction for the first time over the age of 60 years, but these characteristics are not specific enough to identify patients at high risk of cardiac rupture. [11] Most cases of cardiac rupture in which the pericardium is intact are associated with blunt chest trauma or myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%